1991
DOI: 10.1002/jnr.490290316
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a human cDNA expressing a high voltage‐activating. Tea‐sensitive, type‐a K+ channel which maps to chromosome 1 band p21

Abstract: Over ten different mammalian genes related to the Drosophila Shaker gene (the Sh gene family) have been identified recently. These genes encode subunits of voltage-dependent K+ channels. The family consists of four subfamilies: ShI genes are homologues of Shaker; ShII, ShIII, and ShIV are homologues of three other Shaker-like genes in Drosophila, Shab, Shaw, and Shal, respectively. We report here the cloning of a human K+ channel ShIII cDNA (HKShIIIC) obtained from a brain stem cDNA library. HKShIIIC transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 58 publications
4
38
0
Order By: Relevance
“…7,8,[12][13][14]17,18 Moreover, Kv3.4 siRNA nearly ablates the high voltageactivated K C current in small-diameter DRG neurons. 7 Although fast-inactivating slowing of macroscopic inactivation in DRG nociceptors under normal conditions (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…7,8,[12][13][14]17,18 Moreover, Kv3.4 siRNA nearly ablates the high voltageactivated K C current in small-diameter DRG neurons. 7 Although fast-inactivating slowing of macroscopic inactivation in DRG nociceptors under normal conditions (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…8 The Kv3.4 N-terminal inactivation domain (NTID) underlies fast inactivation of the corresponding currents. [12][13][14] Early reports showed modulation of fast Kv3.4 channel inactivation by oxidation, phosphorylation and PIP2 in heterologous expression systems. [15][16][17][18] Demonstrating that inactivation modulation also occurs in neurons, we showed that PKC activation dramatically slows inactivation of the native Kv3.4 channel expressed in DRG nociceptors.…”
Section: Introductionmentioning
confidence: 99%
“…This channel is encoded by hKv3.4, a member of the Shaw subfamily of K + channel genes related to Shaker (Wei et al, 1990;Rudy et al, 1991;Schroter et al, 1991). Comparing the configuration of basic residues at the N-terminus of several inactivating K + channels, we were struck by their close correspondence with unique serine residues in hKv3.4.…”
Section: Introductionmentioning
confidence: 99%
“…The hKv3.4 peptide was based on part of the N-terminal of the deduced sequence of the rapidly inactivating hKv3.4 channel cloned from a human brainstem cDNA library (Rudy, Sen, Vega-Saenz de Miera, Lau, Ried & Ward, 1991) and the rat homologue Raw3 similarly cloned from a rat cortex library (Schrbter, Ruppersberg, Wunder, Rettig, Stocker & Pongs, 1991 Comparison of the actions of hKv3.4 and ShB peptides on mKvl.1…”
Section: Discussionmentioning
confidence: 99%